2006
DOI: 10.1111/j.1365-2648.2006.03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and subjective health among stroke survivors after discharge from hospital

Abstract: Existing Activities of Daily Living scales were expanded and found to relate to a participation scale and a subjective health scale. Using these scales in nursing care has the potential to correct current bias towards functions and activities by broadening the focus to include the social as well as the physical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…A total of 47 papers described the use of ICF in the contexts of a specific health condition, the most frequent being stroke [439,469,470,472,473], multiple sclerosis [444,464,465,467,477], rheumatoid arthritis [440,443,449,454,474], traumatic brain injury [455,457,459] and HIV/AIDS [441,446,447].…”
Section: Clinical Contextsmentioning
confidence: 99%
“…A total of 47 papers described the use of ICF in the contexts of a specific health condition, the most frequent being stroke [439,469,470,472,473], multiple sclerosis [444,464,465,467,477], rheumatoid arthritis [440,443,449,454,474], traumatic brain injury [455,457,459] and HIV/AIDS [441,446,447].…”
Section: Clinical Contextsmentioning
confidence: 99%
“…The relationship between self-efficacy and well-being in stroke survivor's stroke is a leading cause of death in the Western world [1], and is the most common disabling disease, having profound and wide-ranging effects on the physical, psychological and social aspects of an individual's life [2][3][4][5][6]. The focus of health care professionals, particularly early in the period following stroke, is on physical functioning in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed there are attempts to apply the ICF in clinical nursing practice in fourteen selected articles (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In most articles (n=9), ICF application in clinical practice is defined in the Rehabilitation Nursing area (13,(15)(16)(17)(18)(19)(20)(21)26), directed primarily to nursing interventions (n=4) with patients in acute and post-acute situations requiring rehabilitation (13,17) and patients with spinal cord injury (16,21,26).…”
Section: Icf Use In Clinical Nursing Practicementioning
confidence: 99%
“…Two studies conducted at the University Medical Center showed the applicability of the ICF in nursing, with a focus on processes/nursing diagnoses according to the North American Nursing Diagnosis Association (NANDA) Taxonomy II Nursing Diagnoses, their conceptual relations and their use in clinical practice (12,14). It was found that the vast majority of topics addressed in nursing diagnoses can be classified by the ICF and that more identified codes were related to the Body Functions and Activities components (12).…”
Section: Icf Use In Clinical Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation